2003
DOI: 10.1038/sj.sc.3101426
|View full text |Cite
|
Sign up to set email alerts
|

Postacute management of patients with spinal cord injury due to metastatic tumour disease: survival and efficacy of rehabilitation

Abstract: Study design: Retrospective study utilising clinical records and public administration databases. Objectives: This study was performed to analyse the clinical presentation and survival rate of individuals with spinal cord injury (SCI) due to spinal metastasis after primary treatment, and to evaluate the efficacy of rehabilitative efforts. Setting: Spinal Cord Injury Unit, University Hospital, Heidelberg. Methods: A total of 68 consecutive patients were included. Demographics, clinical data, tumour type, level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…The FIM efficiency from our study was 0.38 per day. This value is comparable to those reported in previous studies with metastatic spinal cord injury of 0.33 per day 7 and 0.42 per day. 9 The FIM efficiency was lower in patients with metastatic cancer than in patients with traumatic spinal cord injury, which has been reported as 0.75 per day 10 and 1.3 per day.…”
Section: Discussionsupporting
confidence: 91%
“…The FIM efficiency from our study was 0.38 per day. This value is comparable to those reported in previous studies with metastatic spinal cord injury of 0.33 per day 7 and 0.42 per day. 9 The FIM efficiency was lower in patients with metastatic cancer than in patients with traumatic spinal cord injury, which has been reported as 0.75 per day 10 and 1.3 per day.…”
Section: Discussionsupporting
confidence: 91%
“…To identify patients with long life expectancies who could benefit from such a program, prognostic indicators such as young age, incomplete SCI, good functional status at admission and the scoring system of Tokuhashi et al 29 should be considered. 6,7 …”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12] Most such studies, however, examined metastatic spinal cord compression only, and although they have demonstrated the benefits of rehabilitation in neoplastic patients with regard to pain, independence, prevention of complications and survival, they failed to make comparisons with traumatic SCI (TSCI) patients. [5][6][7][9][10][11][12] Thus, few studies have compared the outcomes of NSCI and TSCI patients, likely because of differences in prognostic factors (age, lesion severity and level, and lesion-to-rehabilitation hospital admission time) between these groups that render them incomparable.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies to date of SCI due to tumour have concentrated on prognostication and functional outcome without examining the effect of pain. Previous studies have usually reported total FIM scores, 10 with only a few reporting separate motor and cognitive subscales. Our results differ from previous studies that reported mean FIM motor gains of 32 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Previous reports on their rehabilitation outcomes have been published. [7][8][9][10] These patients can have a relatively short survival, 11,12 and have a peak age at the time of diagnosis of between 50 and 70 years. 13 With the ageing population and improvements in early cancer diagnosis and treatment leading to increased survival, the number of patients with SCI due to tumour with the potential to benefit from rehabilitation is increasing.…”
Section: Introductionmentioning
confidence: 99%